Cholinesterase inhibitory activity and chemical constituents of Stenochlaena palustris fronds at two different stages of maturity - Chear, Nelson Jeng Yeou; Khaw, Kooi Yeong; Murugaiyah, Vikneswaran; Lai, Choon Sheen (Elsevier, 2016)
Stenochlaena palustris fronds are popular as a vegetable in Southeast Asia. The objectives of this study were to evaluate the anticholinesterase properties and phytochemical profiles of the young and mature fronds of this plant. Both types of fronds were found to have selective inhibitory effect against butyrylcholinesterase compared with acetylcholinesterase. However, different sets of compounds were responsible for their activity. In young fronds, an antibutyrylcholinesterase effect was observed in the hexane extract, which was comprised of a variety of aliphatic hydrocarbons, fatty acids, and phytosterols. In the mature fronds, inhibitory activity was observed in the methanol extract, which contained a series of kaempferol glycosides. Our results provided novel information concerning the ability of S. palustris to inhibit cholinesterase and its phytochemical profile. Further research to investigate the potential use of this plant against Alzheimer's disease is warranted, however, young and mature fronds should be distinguished due to their phytochemical differences.